Promoting effect of mo on pd / g-al2o3 supported catalysts in the oxidative dehydrogenation of propane (2011)
Bimetallic catalysts of Pd-Mo supported on g-Al2O3 were prepared to study the interaction of Pd-Mo in terms of their structural properties and their catalytic activity for the reaction of oxidative dehydrogenation of propane (ODHP). The catalysts contain distributions of Pd- Mo loads between 0 and 5 wt %, and were characterized by total surface area (TSA), total pore volume (TPV), active surface area (ASA), XRD, and TEM-EDS. The results indicate that the addition of Mo to catalysts of Pd/g-Al2O3 modifies its catalytic activity for the ODHP reaction. The influence of the load relationship Pd-Mo in the catalytic activity was determined. Monometallic catalysts were prepared for purposes of comparison.